Hubungan Asupan Makan Dan Status Merokok Dengan Status Gizi Pada Pasien Penyakit Paru Obstruksi Kronik (Ppok) Rawat Jalan Di Rumah Sakit Paru dr. Ario Wirawan Salatiga - Rahayu, Esti, Dwi Sarbini, SST, M.Kes, dr. Listiana D.S, M.Si (2016)
Introduction: Nutrition status on a patient with COPD is an important factor affecting the development of the disease. Poor nutrition status or malnutrition on COPD is caused by decreasing of dietary intake, the increasing energy expenditure, and humoral factors.There are several factors affecting appetite and one of which is smoking status. In Central Java, RSPAW Salatiga is a center of lung and respiratory health care where COPD becomes the first out of ten major deseases of out patient care in RSPAW Salatiga in the last five years. 80% of patients with COPD undergoing out-patient care in RSPAW are in a category of low fat-free mass index. The intake rate of energy, carbohidrat, protein, and fat on patients with COPD undergoing out-patient care in RSPAW categorized low which was 80%, 53% are former smokers and 29% are heavy smokers. Purpose: The purpose of this research was to determine the relationship between dietary intake and smoking status with nutritional status on patients with COPD undergoing out-patient care at RSPAW Salatiga. Method: This was a cross sectional study with consecutive sampling. The subjects of this research were 30 patients with COPD undergoing out-patient care in RSPAW Salatiga who met the criteria of inclusive and exclusive. Dietary intake was obtained by interview and food frequency semi quantitative and smoking status were obtained from quesionaire interview and nutritional status were measured using fat free mass index by using Bioelectrical Impedance Analysis and Microtoice. Data were analyzed using Pearson Product Moment Correlation. Results: 73,4% of the subjects were indicated former-smoker. 53,5% of the subjects were in moderate stage of COPD. 100% of the subjects were in category of low energy intake, 90% of the subjects were in category of low carbohidrate intake, 100% of the subject are in category of low protein intake, 90% of the subjects were in category of low fat intake. 36,7% of the subjects were in category of heavy smoker. 86,7% of the subject are in category of low nutritional status. Conclusion: There was relationship between energy intake and nutritional status (p=0,002, r=-0,532), carbohydrate intake and nutritional status (p=0,005, r=-0,502) and fat intake and nutritional status (p=0,034, r=-0,388). There was no correlation between protein intake and smoking status with nutritional status.